Understanding social innovation in services industries - Gallouj, Faiz; Rubalcaba, Luis; Toivonen, Marja; Windrum, Paul (Taylor & Francis, 2018)
This paper puts forward a framework for understanding the relationship between service industries and social innovation. These are two, previously disconnected research areas. The paper explores ways in which innovation in services is increasingly becoming one of social innovation (in terms of social goals, social means, social roles and multi-agent provision) and how social innovation can be understood from a service innovation perspective. A taxonomy is proposed based on the mix between innovation nature and the locus of co-production. The paper additionally puts forward a theoretical framework for understanding social innovation in services, where the co-creation of innovation is the result of an interaction of competences and preferences of multiple providers, users/citizens, and policy makers. This provides the basis for a discussion of key avenues for future research in theory, measurement, organisation, appropriation, performance measurement, and public policy.